Demographic variation in pain across 22 countries - Lucía Macchia; Chukwuemeka N. Okafor; Thomas Breedlove; Koichiro Shiba; Alan Piper; Byron Johnson; Tyler J. VanderWeele (Communications Medicine)
Abstract Background Recent work has explored the sociocultural aspects of pain. However, global evidence is scarce, and little is known about how levels of pain differ across cultures and across demographic groups within those different cultures. Methods Using a nationally representative dataset of 202,898 individuals from 22 countries and a random effects meta-analysis, we examine the proportion of people in pain across key demographic groups (age, gender, marital status, employment status, education, immigration status, religious service attendance, race/ethnicity) and across countries. Results We find substantial variation in pain across countries and demographic groups. Unadjusted proportions tests show that Egypt (0.60), Brazil (0.59), Australia (0.56), and Turkey (0.53) have the greatest proportion of people in pain whereas Israel (0.25), South Africa (0.29), Poland (0.32), and Japan (0.33) have the lowest proportion. The random effects meta-analysis shows that, across countries, the proportion of people in pain is highest in older age groups, among women and other gender groups, the widowed, those who were retired, those who had low level of education, and those who attended a religious service more than once a week. The analysis shows no difference in the proportion of people in pain regarding immigration status. Conclusions Pain varies substantially across countries and key demographic groups. This work provides valuable foundational insights for future research on the sociocultural factors of pain.